2004
DOI: 10.1029/2003wr002003
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of an island aquifer via tidal methods

Abstract: [1] A set of water level time series collected along a transect through a sedimentary island aquifer was used to test the utility of various simple models of ocean tidal propagation in bounded one-dimensional aquifers. Fourier spectra were calculated for the ocean tidal modes and compared with spectra measured in wells along the island transect. Other sources of fluctuation could be neglected. An observed spatial bias in the well responses (attenuations and lags) could not be modeled by a homogeneous aquifer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
114
3
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 28 publications
(47 reference statements)
6
114
3
5
Order By: Relevance
“…Thus, adequate and reliable aquifer parameters are key to the sustainable management of vital groundwater resources. There are several methods for determining the hydraulic parameters of aquifer systems such as pumping-test or slug-test data analysis (e.g., Freeze and Cherry 1979;Todd 1980;Batu 1998;Butler 1998;Fetter 2000), numerical modeling (e.g., Yeh 1986;Pandit et al 1991;Sun 1994), floodwaveresponse technique (e.g., Pinder et al 1969;Reynolds 1987;Jha et al 2004), and tidal response technique (e.g., Jacob 1950;Ferris 1951;Carr and van Der Kamp 1969;Nielsen 1990;Erskine 1991;Pandit et al 1991;Millham and Howes 1995;Townley 1995;Trefry and Johnston 1998;Shih 1999;Fakir and Razack 2003;Li and Jiao 2003a, b;Teo et al 2003;Trefry and Bekele 2004;Chuang and Yeh 2007;Li et al 2006;Guo et al 2007;Li et al 2007a, b;Ren et al 2007;Xia et al 2007), among others. Out of these methods, the pumping-test data analysis is very popular and is deemed as the standard method to date.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, adequate and reliable aquifer parameters are key to the sustainable management of vital groundwater resources. There are several methods for determining the hydraulic parameters of aquifer systems such as pumping-test or slug-test data analysis (e.g., Freeze and Cherry 1979;Todd 1980;Batu 1998;Butler 1998;Fetter 2000), numerical modeling (e.g., Yeh 1986;Pandit et al 1991;Sun 1994), floodwaveresponse technique (e.g., Pinder et al 1969;Reynolds 1987;Jha et al 2004), and tidal response technique (e.g., Jacob 1950;Ferris 1951;Carr and van Der Kamp 1969;Nielsen 1990;Erskine 1991;Pandit et al 1991;Millham and Howes 1995;Townley 1995;Trefry and Johnston 1998;Shih 1999;Fakir and Razack 2003;Li and Jiao 2003a, b;Teo et al 2003;Trefry and Bekele 2004;Chuang and Yeh 2007;Li et al 2006;Guo et al 2007;Li et al 2007a, b;Ren et al 2007;Xia et al 2007), among others. Out of these methods, the pumping-test data analysis is very popular and is deemed as the standard method to date.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this technique has received less attention and very limited applied studies are reported in the literature. In past studies on coastal aquifer parameter estimation (i.e., inverse modeling) using tide-aquifer interaction technique (Erskine 1991;Pandit et al 1991;Millham and Howes 1995;Jiao and Tang 1999;Trefry and Johnston 1998;Fakir and Razack 2003), except for Shih (1999), Wang and Tsay (2001), Jha et al (2003), Trefry and Bekele (2004) and Li et al ( , 2006Li et al ( , 2007a, it was assumed that the tidal data as such represent sinusoidal waves. In reality, however, the observed tide level consists of several simple harmonic or sinusoidal components (called 'tidal components/constituents') that include the effects of the sun, moon and earth, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1950s, a large number of analytical studies have been conducted on how groundwater responds to tidal fluctuation (Jacob, 1950;Jiao and Tang, 1999;Li et al, 2002Li et al, , 2007Nielsen et al, 1997;Sun, 1997;Townley, 1995;Trefry and Bekele, 2004). Most of these studies assumed that the aquifer is homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Trefry indicated that the complexity of resulting expressions, even for simple composite aquifers, can distract attention from the underlying physics. Trefry and Bekele (2004) evaluated the suitability of various simple models of tidal propagation by using a set of groundwater head time series data collected along a transect in a sedimentary island aquifer near Perth, Western Australia. These researchers concluded that the model that involves composite heterogeneity coincides well with the observed spatial bias in the well responses (attenuations and lags), which cannot be modeled by a homogeneous aquifer theory.…”
Section: Introductionmentioning
confidence: 99%